IDENTIFIKASI JENIS DIPTEROCARPACEAE DI HUTAN LARANGAN ADAT IMBO PUTUI DESA PETAPAHAN KECAMATAN TAPUNG KABUPATEN KAMPAR PROVINSI RIAU - Perkasa, Wahyu Andi; Yoza, Defri; Somadona, Sonia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
ImboPutui Customary Prohibition Forest is located in Petapahan Village, Tapung District, Kampar Regency, RiauProvince. The forest is managed by the local community, with an area of 250 ha.ImboPutui Customary Prohibition Forest is a lowland forest. Based on information from managers in the ImboPutui Customary Prohibition Forest, there are many plants belonging to the Dipterocarpaceae family.There were 9 species of trees belonging to the Dipterocarpaceae family that came from 5 different genera, namely Shorea, Dipterocarpus, Hopea, Parashorea and Dryobalanops. Types of trees found aremeranti kulit buaya, keruing, cingkawang/tengkawang, cengal, kayu batu, meranti bunga, kuras, meranti pirang and meranti batu. Therefore, it is necessary to conduct research with the title Identification of Dipterocarpaceae Types in ImboPutui CustomaryProhibition Forest Petapahan VillageTapung District Kampar Regency Riau Province, which aims to identify the types of Dipterocarpaceae in ImboPutui Customary Prohibition Forest. So that the value of Dipterocarpaceae species diversity at seedlings, saplings, poles and trees in the ImboPutuiCustomary Prohibition Forestis classified as moderate.The highest IKR value for seedlings was merantikulitbuaya and the lowest was cengal. The highest level of stake is merantibunga and the lowest is cengal. The highest pole level is merantibunga and the lowest is kayubatu.The highest level of trees is merantibungaand the lowest is merantibatu.Keywords : Identification, Dipterocarpaceae, Prohibition forest